A Supramolecular Strategy for Self‐Mobile Adsorption Sites in Affinity Membrane. Issue 18 (30th July 2014) - Lin, Ligang; Dong, Meimei; Liu, Chunyu; Wei, Chenjie; Wang, Yuanyuan; Sun, Hui; Ye, Hui
<x xml:space="preserve">Abstract</x> Disclosed here is the design of a novel supramolecular membrane with self‐mobile adsorption sites for biomolecules purification. In the 3D micropore channels of membrane matrix, the ligands are conjugated onto the cyclic compounds in polyrotaxanes for protein adsorption. During membrane filtration, the adsorption sites can rotate and/or slide along the axial chain, which results in the enhanced adsorption capacity. The excellent performance of supramolecular membrane is related with the dynamic working manner of adsorption sites, which plays a crucial role on avoiding spatial mismatching and short‐circuit effect. The supramolecular strategy described here has general suggestions for the "sites" involved technologies such as catalysis, adsorption, and sensors, which is of broad interest. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>